Pengaruh Pemberian Layanan Bimbingan Karir Terhadap Perencanaan Karir Siswa Kelas XI MAN 2 Deli Serdang - Sembiring, Azura Mahyuliza; Lubis, Saiful Akhyar; Nasution, Fauziah (Ikatan Da'i Indonesia, 2024)
This exploration is supposed to affect giving professional direction on the expert settings of class XI understudies at MAN 2 Deli Serdang. This assessment utilizes a quantitative system with a semi-preliminary procedure. The populace utilized in this investigation was 36 understudies and the examples utilized in this test were 36 respondents who utilized sporadic testing techniques. The data assortment technique utilized a survey which was circulated to 36 respondents from class XI IIS 2 MAN2 Toko Serdang understudies. The data checking system utilized is a firm authenticity and quality test, sensibility test, linearity test, speculative test. The data utilized in this test board is the SPSS structure 20 application. The consequences of this investigation utilized IBM SPSS Estimations version 20 and got a rcount of 0.342 and r table 0.329, there is a relationship impact of 0.342 > 0.05 at a degree of data significance of 5% and on collaboration in the low grouping. In view of the consequences of the assessment over, the hypothesis endeavored by the master will in general be thought of as right.